2021
DOI: 10.1123/jsr.2021-0043
|View full text |Cite
|
Sign up to set email alerts
|

Weak Hip Strength Increases Dynamic Knee Valgus in Single-Leg Tasks of Collegiate Female Athletes

Abstract: Clinical Scenario: Dynamic knee valgus (DKV) is a mechanical alteration in the knee that leads to increased risk of injury. Weakness of hip musculature in hip abduction (HABD), extension (HEXT), and external rotation (HER) may contribute to increased DKV in single-leg landing tasks. Focused Clinical Question: Is decreased hip strength associated with an increase in DKV during a single-leg landing task in collegiate female athletes? Summary of Key Findings: Three studies were included: One randomized control tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Several studies on the visual assessment of the LSD have shown that poor performance is associated with reduced ADF [ 31 , 78 , 86 , 87 ], while a study on the FSD [ 14 ] and one on the SLS [ 88 ] do not support this. Furthermore, quantitative studies using 3-dimensional analysis on both healthy subjects and those with a knee condition suggest that poor performance in the SLS, LSD, and FSD is associated with reduced ADF [ 11 , 12 , 89 ]. The reason for the non-significant association in the present study might be related to the relatively good ankle mobility displayed by this sample of female soccer players, as well as the lack of contrast in our data, as the range of data was small, which might have hampered the possibility of finding significant associations with the outcome of the SLS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the visual assessment of the LSD have shown that poor performance is associated with reduced ADF [ 31 , 78 , 86 , 87 ], while a study on the FSD [ 14 ] and one on the SLS [ 88 ] do not support this. Furthermore, quantitative studies using 3-dimensional analysis on both healthy subjects and those with a knee condition suggest that poor performance in the SLS, LSD, and FSD is associated with reduced ADF [ 11 , 12 , 89 ]. The reason for the non-significant association in the present study might be related to the relatively good ankle mobility displayed by this sample of female soccer players, as well as the lack of contrast in our data, as the range of data was small, which might have hampered the possibility of finding significant associations with the outcome of the SLS.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the higher degree of knee valgus noted in the female players in the present study may be that their relative strength was significantly lower than the male player’s. Previous research has noted that weak hip abductors can lead to increased knee valgus [ 17 , 48 ] and the hip abductors are a muscle group that is largely recruited during a squat [ 49 ]. Thus, one explanation for the women’s inferior relative strength could be that they were weaker than the men in the hip abductors and therefore demonstrated greater knee valgus.…”
Section: Discussionmentioning
confidence: 99%
“…Hip-muscle weakness is associated with knee OA [38]. Decreased hip abductor, extensor, and external rotator strength can lead to dynamic knee valgus [39,40]. Hence, the straight-stem surgical approach is associated with knee arthritis and valgus configuration.…”
Section: Discussionmentioning
confidence: 99%